2022
DOI: 10.26508/lsa.202101348
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and compound screens uncover factors modulating cancer cell response to indisulam

Abstract: Discovering biomarkers of drug response and finding powerful drug combinations can support the reuse of previously abandoned cancer drugs in the clinic. Indisulam is an abandoned drug that acts as a molecular glue, inducing degradation of splicing factor RBM39 through interaction with CRL4DCAF15. Here, we performed genetic and compound screens to uncover factors mediating indisulam sensitivity and resistance. First, a dropout CRISPR screen identified SRPK1 loss as a synthetic lethal interaction with indisulam … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Observed interaction scores range from −9.63 (for HROBML01 and the combination of cisplatin with vinorelbine) to 10.95 (for HROLu22 and the combination carboplatin with vinorelbine). Most studies suggest a cutoff at about −10 and 10 ( 46 48 ) for calling synergy or antagonism, respectively. None of the tested combinations largely surpass these values; thus, observed effects were most likely additive.…”
Section: Resultsmentioning
confidence: 99%
“…Observed interaction scores range from −9.63 (for HROBML01 and the combination of cisplatin with vinorelbine) to 10.95 (for HROLu22 and the combination carboplatin with vinorelbine). Most studies suggest a cutoff at about −10 and 10 ( 46 48 ) for calling synergy or antagonism, respectively. None of the tested combinations largely surpass these values; thus, observed effects were most likely additive.…”
Section: Resultsmentioning
confidence: 99%
“…By studying molecular markers in glioma tissues, we can better understand the mechanisms of tumor development, prognosis assessment, and the formulation of personalized treatment plans. Current research has identified therapeutic methods such as TERT (telomerase reverse transcriptase) promoter mutations [23][24][25], IDH1/2 (isocitrate dehydrogenase 1) mutations, and 1p/19q co-deletion [26,27]; corresponding treatments have been applied in clinical practice. Despite achieving a series of treatment outcomes, the prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…Under normoxic and moderately hypoxic conditions, knocking down SRPK1 inhibits the malignant progression of glioma cells [21,22], induces apoptosis in glioma cells [21,23], and suppresses AKT/E1F4E phosphorylation [21]. Plexin B1 promotes SRPK1 activity through the PI3K/AKT signaling pathway, thereby increasing cell growth, angiogenesis, and motility in vitro and in vivo [21,24]. However, the specific mechanism by which SRPK1 regulates glioma cell proliferation remains unclear, and there is still an urgent need to continue exploring SRPK1-related signaling pathways in gliomas to find new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It was further suggested the increased sensitivity could stem not only from high DCAF15 levels but from the need for timely mRNA processing in Myc-driven neuroblastoma. A more recent preprint used a CRISPR dropout screen in the lung cancer cell line A549 to identify the Serine/Arginine (SR) protein kinase 1 (SRPK1), which is specific to the SR family of splicing factors as a synthetic lethal interaction of ArSulf treatments ( 45 ). Taken together, these findings suggest that the splicing targets of RBM39 and any possible crosstalk amongst splicing factors need to be looked at carefully to identify cell lines or cancers that would be particularly intolerant of RBM39 downregulation.…”
Section: Discussionmentioning
confidence: 99%